Three New Sidewalk Inscriptions from Caesarea Maritima. - Gersht, Rivka; Gendelman, Peter (Scripta Classica Israelica, 2025)
The three tessellated sidewalk inscriptions were exposed by the Israel Antiquities Authority archaeologists between 2008 and 2023. Two of the inscriptions, dating from mid-5th-early 6th century CE, are fully preserved; of the third inscription, dating from 3rd-4th century CE, the first seven letters preserved. Both Late Antique inscriptions mention an individual named Elias who built a construction, probably at his own cost. The differences between the two inscriptions--in style, technique and the title comes mentioned in only one--raise questions regarding the dating of the inscriptions, the identity and status of Elias in each inscription, and the kind of constructions built. With regard to the Roman Period inscription, in spite of its state of preservation, and the fact that only a section of the sidewalk was excavated and almost nothing of the adjacent construction, it may be assumed that Sillios/Sillius, the individual whose name is mentioned in the inscription, constructed the sidewalk or the structure which faced the inscription. While studying the three inscriptions we looked for similar sidewalk formulas and for the prevalence, forms and origin of the names mentioned in the inscriptions among Jews, Pagans and Christians in the region and beyond.